2008
DOI: 10.1534/genetics.108.089243
|View full text |Cite
|
Sign up to set email alerts
|

Rtf1-Mediated Eukaryotic Site-Specific Replication Termination

Abstract: The molecular mechanisms mediating eukaryotic replication termination and pausing remain largely unknown. Here we present the molecular characterization of Rtf1 that mediates site-specific replication termination at the polar Schizosaccharomyces pombe barrier RTS1. We show that Rtf1 possesses two chimeric myb/SANT domains: one is able to interact with the repeated motifs encoded by the RTS1 element as well as the elements enhancer region, while the other shows only a weak DNA binding activity. In addition we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 51 publications
(75 reference statements)
0
33
0
Order By: Relevance
“…In budding yeast, a single replication terminator protein called Fob1 binds to the Ter sites (RFBs) located in nontranscribed spacer 1 (NTS1) of rDNA to cause polar fork arrest (10,11), which prevents transcription-replication collision, fork stalling, and genome instability. Fission yeast has three known terminator proteins: Rtf1, which functions at the mating-type switch locus (12,13), and Reb1 (Sp. Reb1) and Sap1, which act at the Ter sites of rDNA spacers (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…In budding yeast, a single replication terminator protein called Fob1 binds to the Ter sites (RFBs) located in nontranscribed spacer 1 (NTS1) of rDNA to cause polar fork arrest (10,11), which prevents transcription-replication collision, fork stalling, and genome instability. Fission yeast has three known terminator proteins: Rtf1, which functions at the mating-type switch locus (12,13), and Reb1 (Sp. Reb1) and Sap1, which act at the Ter sites of rDNA spacers (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…This composite DBD arrangement appears to be conserved in all of the different members of the terminator protein family. Secondary structure prediction and domain mapping studies of TTF-I and Rtf1 showed that protein constructs with impaired DNA binding properties have deletions in regions that we now predict to have the first MybAD (27,38). The alignment shows structural differences among family members in the composite DBD.…”
Section: Structure Of Reb1 Defines the Prototypic Architecture Of A Ementioning
confidence: 87%
“…1 region that may be involved in oligomerization (27,(37)(38)(39)(40) and two or more Myb-like sequence-specific DNA binding domains at the C terminus. However, additional regions located immediately N-terminal to the predicted Myb domains are also needed for full binding affinity (37,39).…”
Section: Significancementioning
confidence: 99%
“…Interestingly, S. pombe RTS1, another natural RFB located in the mating-type locus, determines the appropriate direction of replication of this region required for efficient mating-type switching (Dalgaard and Klar, 2001). Rtf1 is a DNA-binding protein responsible for the function of RTS1 that shows a high similarity to Reb1 (Eydmann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%